Panel Data Regression Modeling of the GRDP of Banten Province for the Years 2016-2020 - Alfa Puspita Swasti Anggraini; Khikmah, Laelatul (Institut Teknologi Statistika dan Bisnis Muhammadiyah Semarang, 2023)
Banten is one of the provinces on the island of Java. Banten's Economy in 2020 decreased by 3.38 percent, even though in 2019 it still grew to 5.29 percent. This decline was also deeper than the National which only decreased 2.07 percent. Gross Regional Domestic Product (GDP) is one of the important indicators to determine the economic condition in an area or province in a certain period. Panel data is a combination of time data series and cross sections. Panel data regression is a regression by combining data cross section and time series in an equation. In this study, analysis was carried out panel data regression to determine the variables that affect the GRDP of Banten Province. The results of the analysis show that the best panel data regression model is Random Effect Model (REM). Variables that affect the GRDP of Banten Province are Total Residents and Domestic Investment.